GAYA BERILOKUSI USTAD ADI HIDAYAT PADA VIDEO CERAMAH “DZIKIR PENUNTAS KEGELISAHAN” DI MEDIA DIGITAL YOUTUBE (USTAD ADI HIDAYAT'S ILLOCUTIONAL STYLE ON THE VIDEO OF THE “DZIKIR PENUNTAS KEGELISAHAN” ON YOUTUBE) - Deasy Wahyu Hidayati (Universitas Lambung Mangkurat, 2023)
AbstractUstad Adi Hidayat's Illocutional Style On The Video Of The “Dzikir Penuntas Kegelisahan” On Youtube. Ustad Adi Hidayat (UAH) is one of the popular lecturers who conveys religious ideas in a gentle and tolerant manner so that many people like him. UAH and the team manage YouTube as a medium for lectures on a digital platform. Therefore, this study will analyze UAH's illocutionary style in his video lectures on the official YouTube channel